HOMESICKNESS SYNDROME OF BOARDING SCHOOL STUDENTS AT ONE BOARDING SCHOOL IN KANCHANABURI PROVINCE - Tancharoensuk, Khunita; Thongpak, Nithis; Tiamtiporn, Warittha (Academic Journal of Thailand National Sports University, 2022)
The purposes of this research were to 1) study the effects of homesickness syndrome on the life of boarding school students, and 2) study the adaptation guidelines for boarding school students with homesickness. The research was a qualitative research. The subjects were 2 grade 7 students at one boarding school in Kanchanaburi Province.The research instruments included The Homesickness Questionnaire: HQ and semi - structured interview form. The data were analyzed using content analysis. The results of research were found that: homesickness affected life in a boarding school students, especially when they first moved in. This was because students were unable to adapt to the new environment and the strict rules of boarding school. This school did not allow students to use their phones as well as, parents were not allowed to visit them during the first month. Afterward, students made better adjustments, such as taking up hobbies, keeping busy, talking to friend and avoiding friends, who asked about their family. By doing so, their homesickness symptoms were better.